Simple solutions for complex problems? What is missing in agriculture for nutrition interventions - Caroline Hambloch; Kai Mausch; Costanza Conti; Andy Hall (Food Security, 2022)
Abstract Within the nutritionism paradigm, in this article we critically review the marketization and medicalization logics which aim to address the pressing issue of malnutrition in low- and middle-income countries. Drawing from political economy and food system transformation discourses, we are using the popular intervention types of nutrition-sensitive value chains (marketization logic) and biofortification exemplified through orange-fleshed sweet potato (medicalization logic) to assess their outcomes and underlying logics. We demonstrate that there is insufficient evidence of the positive impact of these interventions on nutritional outcomes, and that their underlying theories of change and impact logics do not deal with the inherent complexity of nutritional challenges. We show that nutrition-sensitive value chain approaches are unable to leverage or enhance the functioning of value chains to improve nutritional outcomes, especially in light of the disproportionate power of some food companies. We further demonstrate that orange-fleshed sweet potato interventions and biofortification more broadly adopt a narrow approach to malnutrition, disregarding the interactions between food components and broader value chain and food system dynamics. We argue that both intervention types focus solely on increasing the intake of specific nutrients without incorporating their embeddedness in the wider food systems and the relevant political-economic and social relations that influence the production and consumption of food. We conclude that the systemic nature of malnutrition requires to be understood and addressed as part of the food system transformation challenge in order to move towards solving it. To do so, new evaluation frameworks along with new approaches to solutions are necessary that support multiple and diverse development pathways, which are able to acknowledge the social, political-economic, and environmental factors and drivers of malnutrition and poverty.
Keywords: 330; Food systems; Nutrition-sensitive; Value chains; Biofortification; Orange-fleshed sweet potato; Political economy